2019
DOI: 10.1080/1331677x.2019.1642785
|View full text |Cite
|
Sign up to set email alerts
|

Profitability determinants of hotel companies in selected Mediterranean countries

Abstract: Tourism is one of the most important industries in the Mediterranean countries, which strongly contributes to the economic activity, capital investment and job creation. Therefore, the purpose of this paper is to examine the determinants influencing profitability of hotel companies in selected Mediterranean countries. Thereby, dynamic panel data models are estimated on an extensive dataset for the period from 2007 to 2015. The paper provides evidence on differences among internal profitability determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 33 publications
2
33
0
4
Order By: Relevance
“…Pereira-Moliner et al (2011) stated the same conclusion in a sample of hotels. The difference in hotel profitability was also confirmed by Dimitric et al (2019) who dealt with hotels in selected Mediterranean countries. Our findings complement the conclusions by Costa and Costa (2019), who confirmed the differences in financial health in the tourism sector and stated that hotels show better financial performance compared to the group of enterprises engaged in other tourism activities.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Pereira-Moliner et al (2011) stated the same conclusion in a sample of hotels. The difference in hotel profitability was also confirmed by Dimitric et al (2019) who dealt with hotels in selected Mediterranean countries. Our findings complement the conclusions by Costa and Costa (2019), who confirmed the differences in financial health in the tourism sector and stated that hotels show better financial performance compared to the group of enterprises engaged in other tourism activities.…”
Section: Resultsmentioning
confidence: 74%
“…Pereira-Moliner et al (2011) as well as McNamara et al (2003) highlighted the possible causes of the differences, and the bargaining power of businesses can be considered as one of the main causes. Dimitric et al (2019) confirmed the difference in the profitability of hotels in selected Mediterranean countries (Croatia, Greece, Spain and Portugal) using indicators such as ROA, cash flow operating revenue, net asset turnover, solvency ratio, while their findings showed that the cash flow to operating revenue had a statistically significant and positive impact on profitability. Simultaneously, the authors emphasized the significance of the overall ratio of asset turnover to solvency.…”
Section: Literature Reviewmentioning
confidence: 65%
“…Tourism plays a pivotal role to several countries. It is a source of foreign exchange, employment, infrastructure development, investments, innovation and enterprise development therefore becoming a vital driver of socio-economic advancement and poverty reduction [1,2,3]. The dynamics of the global tourism is swayed by external factors (globalisation, new technology, modernisation in transport and communications systems) as well as internal factors (new tourist demands and more flexible management) [1].…”
Section: Background Of the Studymentioning
confidence: 99%
“…It is a source of foreign exchange, employment, infrastructure development, investments, innovation and enterprise development therefore becoming a vital driver of socio-economic advancement and poverty reduction [1,2,3]. The dynamics of the global tourism is swayed by external factors (globalisation, new technology, modernisation in transport and communications systems) as well as internal factors (new tourist demands and more flexible management) [1]. Tourism is expected to play a pivotal role in ensuring the Kenyan economy grows at the projected rate of 10% per annum up to the year 2030 and it can be noted that factors that included political stability, improved security situation, growth in the aviation sector, investor confidence, withdrawal of travel advisories, visits by foreign dignitaries, open border policy, hosting of international conferences improved Kenya's tourism performance in 2018 [3,4].…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation